Janowski subclasses of starlike mappings - CURT, Paula (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, two subclasses of biholomorphic starlike mappings named Janowski starlike and Janowski almost starlike with complex parameters are in- troduced and studied. We determine M such that holomorphic mappings f which satisfy the condition lDf (z) − Il ≤ M , z ∈ Bn, are Janowski starlike, respectively Janowski almost starlike. We also derive sufficient conditions for normalized holomorphic mappings (expressed in terms of their coefficient bounds) to belong to one of the subclasses of mappings mentioned above. Mathematics Subject Classification (2010): 32H02, 30C45. Received 19 February 2022; Accepted 17 March 2022.